Need Analysis of Indonesian Language Teaching Book Development For Implementation of Merdeka Belajar Kampus Merdeka - Resnita Dewi; Anastasia Baan (Universitas Cokroaminoto Palopo, 2021)
This research aims to reveal the analysis of needs in developing teaching books Indonesian. This research is the first stage of teaching book development research using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. This stage of analysis is done to analyze the importance of doing this research. Needs analysis includes (1) analysis of curriculum; (2) analysis of student needs; (3) Analysis of student characteristics. The data in the study was collected with observation techniques, interviews, and questionnaires